(untitled) (Confluenţe Bibliologice, 2022)
The researchers presents information about the valuable works of Bessarabian writers from the collection of rare documents of SL USARB. The collection is a source of information about the political, social and cultural phenomenon that took place in Bessarabia, reﬂected in the books of Bessarabian writers being a good chance for students to research and study the books of Bessarabian writers.